Traumatic cardiac herniation presenting as dextrocardia: A case report (Indian Journal of Case Reports, 2016)
Background: Cardiac herniation is a rare but significant complication of blunt traumatic pericardial rupture most commonly occurring as a result of high-energy road traffic accidents. Case reports to date highlight delays in diagnosis and management as well as high rates of morbidity and mortality. Case presentation: A 19 year old motorcyclist was brought into the emergency department via helicopter following a road traffic accident with severe injuries to his chest, abdomen and limbs. Following a period of haemodynamic instability, an urgent chest radiograph demonstrated new dextrocardia compared to his admission radiograph. A diagnosis of cardiac herniation was confirmed and the patient underwent emergency surgery with a mesh repair within 12 hours of his initial presentation. He made a full recovery from a cardiothoracic perspective and was well at follow up three months after discharge. Conclusions: Pericardial rupture and cardiac herniation should be considered urgently in the context of abnormal cardiac anatomy on imaging following blunt trauma. Here, we describe a case of prompt identification and definitive surgical intervention for cardiac herniation. The diagnosis was made following a chest radiograph showing new dextrocardia and the patient had a good clinical outcome.